Stolen Ukrainian universities: An invisible russian weapon - Alex Plastun; Serhiy Kozmenko (Problems and Perspectives in Management)
This paper explores the issue of “stolen” Ukrainian universities. Over 1,500 Ukrainian educational and research organizations have been seized by Russia, including 289 higher education institutions such as universities, institutes, academies, colleges, and their branches. These institutions are now exploited to further Russia’s geopolitical agenda through propaganda, territorial annexation justification, and the assimilation of the Ukrainian population in occupied regions. The study examines this using the following examples: the perception of stolen Ukrainian universities as Russian entities by international organizations and academic communities; recognition of stolen Ukrainian intellectual property as Russian, with silent approval or facilitation, such as the registration and confirmation of stolen Ukrainian academic journals by the International ISSN Centre. The paper highlights the use of these stolen institutions’ resources as propaganda tools, their role in ideological manipulation, and their contribution to the assimilation of occupied territories. Recommendations include removing stolen universities from academic affiliations and databases, revoking ISSN registrations for stolen Ukrainian journals, and urging COPE to issue ethical guidelines for preventing collaboration with stolen universities. Additionally, it emphasizes the need for Ukrainian authorities and the academic community to engage proactively with global publishing institutions, database owners, and organizations handling publishing ethics to address these challenges. By bringing attention to this “silent war on knowledge”, the paper underscores the urgency of addressing the misuse of stolen academic institutions by Russia to uphold the integrity of global academia and international law.